2016
DOI: 10.1051/parasite/2016020
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofKudoa septempunctatagenotype ST3 isolate from Korea on ddY suckling mice

Abstract: -This study investigated the effects of Kudoa septempunctata genotype ST3 spores on ddY suckling mice. Purified Kudoa septempunctata spores were administered into the stomachs of the mice at 5 · 10 6 or 5 · 10 7 spores/ mouse, with inactivated Kudoa (5 · 10 6 spores/mouse) or vehicle as controls. No abnormal clinical symptoms were observed and there were no variations in fluid accumulation ratio and cytokine gene expression in all groups. In addition, intact Kudoa spores and the 18S rDNA gene were only detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…1A), which was consistent with previous reports [1, 7]. Control spores with nuclei exhibiting only blue fluorescence (Hoechst 33342 positive and PI negative) were considered viable (Figs.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…1A), which was consistent with previous reports [1, 7]. Control spores with nuclei exhibiting only blue fluorescence (Hoechst 33342 positive and PI negative) were considered viable (Figs.…”
Section: Resultssupporting
confidence: 90%
“…The spore genotypes were assessed by conventional PCR to amplify the cytochrome c oxidase subunit I ( cox 1 ; 751 bp) and large subunit rRNA ( rnl ; 817 bp) of the K. septempunctata mitochondrial gene [17]. The primer sets used were cox 1 -F1 (5′-TTTGTTCATCGGCACAATTC-3′), cox 1 -R1 (5′-ATAGCCTGGAACAAGGAATC-3′), rnl -F1 (5′-TGCCGTCATTCTGTTGTATT-3′), and rnl -R1 (5′-AATACCCATGCTGTGTTCAT-3′), as described in previous reports [1, 7, 17]. Negative controls (without template DNA) were included to check for contamination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kawai et al [2] reported that diarrhea was induced in 4-5-day-old mice infected with K. septempunctata ; however, the remaining studies used the same methodology and showed conflicting results [7,8]. Overall, our findings suggest that the evidence for the pathogenicity of K. septempunctata is still weak, in light of the currently available literature.…”
Section: Conclusion and Suggestionmentioning
confidence: 61%
“…Although the subjects and experimental methods in the study by Jang et al [7] were the same as those in the study by Kawai et al [2], the results differed. Kawai et al [2] were Japanese and claimed that the pathogenicity of K. septempunctata caused the outbreak of acute food poisoning; the authors of the other studies were Chinese and Korean.…”
Section: Evaluation Of the Related Evidencesmentioning
confidence: 99%